PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS-GAMES-TOURNAMENT (TGT) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 2 MUNGKA - Yande, Syafwa; Delsi K, Delsi K; Fitri, Dewi Yuliana (STKIP PGRI Sumbar, 2014)
ABSTRACT The background of this research was the lack of understanding of mathematical concepts students and students would rather sit down and resolve the problem that was given to the teacher or a friend bench next to his friend, in discussing the matter dominated by active alone. This study aim to determine whether students mathematical understanding of the concept of class IX SMP 2 Mungka Fifty city districts with implementing Learning Strategy Team Game Tournament Type Kooperatife beter than convetional learning. Based on the analysis of data it was known that the two classes were normally distributed and homogeneous samples at significance level α = 0.05 and the results obtained from testing the hypothesis P-value = 0.023. It can be concluded that the students understanding of mathematical concepts apply Kooperatife Learning Strategy Game Tournament Team Type better than conventional teaching students IX SMP 2 Mungka City District Fifty Lessons Year 2013/2014.